2020
DOI: 10.1101/2020.01.29.919993
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delivery mode impacts newborn gut colonization efficiency

Abstract: Delivery mode is the variable with the greatest influence on the infant gut microbiome composition in the first few months of life. Children born by Cesarean section (C-section) lack species from the Bacteroides genus in their gut microbial community, and this difference can be detectable until 6-18 months of age. One hypothesis is that these differences stem from lack of exposure to the maternal vaginal microbiome, as children born by C-section do not pass through the birth canal; however, Bacteroides species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 27 publications
(47 reference statements)
1
20
1
Order By: Relevance
“…These findings complement those from other studies that demonstrated that maternal gut microbes can be transmitted to infants via vaginal delivery (35,36). Transmission and colonization of the maternal gut microbiota in infants delivered vaginally is thought to have protective and advantageous functions, as these microbiota are suited to the environment of the gut and have the capacity to contribute to nutrient acquisition in early life (28).…”
Section: Delivery Mode the Gut Microbiota And Health Outcomes The Esupporting
confidence: 85%
See 3 more Smart Citations
“…These findings complement those from other studies that demonstrated that maternal gut microbes can be transmitted to infants via vaginal delivery (35,36). Transmission and colonization of the maternal gut microbiota in infants delivered vaginally is thought to have protective and advantageous functions, as these microbiota are suited to the environment of the gut and have the capacity to contribute to nutrient acquisition in early life (28).…”
Section: Delivery Mode the Gut Microbiota And Health Outcomes The Esupporting
confidence: 85%
“…However, two recent studies of the neonate gut microbiota showed that the prevalence and abundance of Lactobacillus species were similar in both vaginally delivered and C-section groups (27,28). Instead, Bifidobacterium, Escherichia, Bacteroides, and Parabacteroides species ( Table 1) were enriched in the gut microbiota of vaginally delivered infants, and were possibly inherited from maternal fecal microbes (27,28). These findings complement those from other studies that demonstrated that maternal gut microbes can be transmitted to infants via vaginal delivery (35,36).…”
Section: Delivery Mode the Gut Microbiota And Health Outcomes The Ementioning
confidence: 99%
See 2 more Smart Citations
“…Our observation that the sow gut microbiome was influenced by parity, together with recent evidence suggesting that maternal gut microbes are likely candidates for vertical transmission to offspring [33, 34], prompted us to characterize the relationship between maternal and offspring gut microbes. As expected, Bray-Curtis beta diversity analysis of metagenomic data from piglets born to each sow (n=54) showed that maternal gut microbiomes were markedly distinct from those of the piglet gut ( P =1e-5, R 2 =0.27), such that the gut microbiome composition of a sow is more similar to that of other sows than to that of her infant offspring (SFig 3A) .…”
Section: Resultsmentioning
confidence: 99%